PERAN FASILITATOR DALAM PROSES DIVERSI PADA KASUS ANAK SEBAGAI PELAKU TINDAK PIDANA PENCURIAN DENGAN KEKERASAN - Mujita Sekedang; Alvi Syahrin; Muhammad Hamdan; Marlina Marlina (USU LAW JOURNAL, 2018)
ABSTRACT Nowadays, theft with violence is rapidly increasing, and it highly alarms people. Generally it is committed by adults, but lately it has turned to be committed by children or even minors. Some of their victims are wounded or even killed. Child Criminal Judicial Administration is usually used to handle theft with violence committed by children. It is not merely intended to impose criminal sanctions on children who have committed theft by violence. It is known as the term, ‘diversion’ which is a process of diverting from the process of Judicial Administration. Diversion has to be performed toward children who have committed criminal acts, and it is done through the stage of pre-investigation, investigation, prosecuting, and the stage of Judicial Administration in the District Court. The research used juridical normative and juridical empirical with descriptive analytic methods. The data were gathered by conducting library research and legal documentary study and analyzed qualitatively in which the legal materials were analyzed qualitatively, using deductive and inductive methods so that the conclusion would be accurate and scientifically accounted for.  A judge is required to offer to a child perpetrator, and/or his parents/guardian, and the victim to settle the case through diversion. When they do not come to a consensus, the Judge will bring the case to the Court (litigation). When they agree to do diversion, diversion negotiation will be led by the Judge, and when the consensus of opinion occurs, the result has to be presented to the Head of District Court who controls the implementation of the diversion. The role of a facilitator in the process of diversion in the case of a child who commits theft with violence in the Medan District Court is active. In his role, the Judge attempts to ask both parties for negotiation, without litigation, for the sake of the child. Why diversion is not done in the three cases because the Judge who pronounces judgment on the three cases tends to use legal positivism without paying more attention to the interest of the child as the perpetrator of theft criminal act with violence, whereas Law No. 11/2o12 on SPPA confirms that a Judge who pronounces judgment on children is required to emphasize on the interest of children.   Keywords: theft with violence, diversion, facilitator.